Relações entre mobilização dos registros de representação semiótica e os níveis de letramento estatístico com duas professoras - Freitas, Eliana Maria Bauschert de (2010)
The purpose of this project was to verify the level of statistical literacy of two teachers of the High School which work with statistics. Also, tired to extensity the influence of the use of computational environment, in case software FATHOM, in the evolution of the levels of graphical reading and, consequently, literacy, using simultaneous and differents registers of semiotic representation. We found to answer these questions: Which is the level of statistic literacy of the Mathematics teachers in High School who works with Descriptive Statistic? How these people perceive the simultaneous use of different registers of semiotics representation for analysis of a data set, with or without the use of computational environment? For these were used the methodology Didactics Engineering, developing a study of case with two mathematics teachers of the High School who had already worked with some concepts of Descriptive Statistic in their courses. The analysis of the interviews allowed to notice that the teachers oscillated between the levels of scientific literacy and functional literacy and the use of the software made easier the perception of the necessity and advantages to work simultaneously with more one register of semiotic representation